2018
DOI: 10.1002/hed.25088
|View full text |Cite
|
Sign up to set email alerts
|

Narrow band imaging for head and neck malignancies: Lessons learned from mistakes

Abstract: The WLE + NBI improved diagnostic accuracy, but not all lesions were ideally evaluated with current defined patterns. An accurate anamnesis is mandatory, because, in some cases, it may be more relevant than the NBI pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…This is an extremely rare tumour, accounting for less than 1% of all laryngeal cancers [21]. One description of the appearance of the neuroendocrine tumour seen in NBI is given in the literature, concerning the lesion localised in the intestinal lumen [22] and in the area of the head and neck [19]. The authors have not observed any characteristic vascularisation that confirms the malignant nature of the lesion.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…This is an extremely rare tumour, accounting for less than 1% of all laryngeal cancers [21]. One description of the appearance of the neuroendocrine tumour seen in NBI is given in the literature, concerning the lesion localised in the intestinal lumen [22] and in the area of the head and neck [19]. The authors have not observed any characteristic vascularisation that confirms the malignant nature of the lesion.…”
Section: Methodsmentioning
confidence: 94%
“…Valls-Mateus et al [19] attempted to answer the question of what is the most difficult according to NBI endoscopy. They assessed the characteristic features for false positive and false negative diagnoses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four of the five included studies reported measures of NBI diagnostic accuracy between LP and LSCC [ 7 , 10 , 12 , 13 ]. Studies were consistent to confirm high SE of NBI both for LP (92–94%) and LSCC (92–100%), better for the latter.…”
Section: Resultsmentioning
confidence: 99%